Management of cooperation between customer and outsourcer in the project with using the software products - Саінчук, Аріадна Олександрівна (Eastern-European Journal of Enterprise Technologies, 2011)
In the project management there exists the definition of outsourcer. The schemes were compiled: transferring functions between customer, outsourcer, sub-outsourcer, to transfer the exchange forms between customer, outsourcer, sub-outsourcer with help of component of the mailing